SOCIAL ADAPTATION AND ROLE DYNAMICS AS PREDICTORS OF BULLYING BEHAVIOR IN YOUNG SCHOOL-AGED CHILDREN - Berdiyeva Gulmira Juraevna; Sabirova Manzura Arif qizi (Innovate Conferences, 2025)
This paper explores the connection between social adaptation and the emergence of bullying behavior among primary school students. The research focuses on how social roles within classroom groups—leaders, followers, isolates, and neutrals—contribute to the formation and continuation of aggressive or passive behaviors. The study was conducted in three primary schools, involving 98 students aged 7 to 11, along with teacher evaluations and structured sociometric testing. Results revealed that students poorly integrated into peer networks, especially those classified as 'isolates', were either frequently bullied or showed reactive aggression. Meanwhile, those with strong group identity or leadership roles were more likely to exhibit dominant or controlling behaviors. The study advocates for improving peer acceptance and restructuring classroom social interactions to prevent bullying.
Keywords: social adaptation, school roles, peer dynamics, bullying, sociometry, classroom hierarchy.